Evaluation of a First Peoples-led, emotion-based pedagogical intervention to promote cultural safety in undergraduate non-Indigenous health professional students. (February 2022) - Mills, Kyly; Creedy, Debra K.; Sunderland, Naomi; Allen, Jyai; Carter, Amanda; Corporal, Stephen
Abstract: Background: Undergraduate health students learn cultural safety in complex and emotional ways. Pedagogies that account for these complexities must be developed and evaluated. Objectives: To evaluate a First Peoples-led emotion-based pedagogical intervention on non-Indigenous health professional students' development towards cultural safety. Design: A pre-post mixed-methods intervention design. Setting and participants: All undergraduate health students undertaking a semester-long First Peoples cultural safety course ( n  = 395) were invited to participate. Methods: The intervention involved students' written reflections and comfort (1 = very uncomfortable to 5 = very comfortable) with workshop content, using a gawugaa-gii-mara (head, heart, hands) form. The educator analysed student responses collected on the form, to prompt discussion in a series of four workshops. Students also completed the online 20-item Student Emotional Learning in Cultural Safety Education Instrument (SELCSI) which has two scales, Witnessing and Comfort. gawugaa-gii-mara responses were thematically coded. Paired sample t -tests examined differences over time. Eta squared determined effect size. Results: There were 102 matched pre-post-intervention surveys. Both SELCSI scales had excellent internal consistency (Witnessing α = 0.80, Comfort α = 0.92). A statistically significant difference was observed between students' mean scores on the Witnessing scale prior to the course (M = 47.10, SD = 6.51) compared to post-course (53.04, SD = 4.80), t(95) = 8.70, p  < 0.001 (two-tailed) with a large effect size (d = 0.88). Most Comfort scale items increased but were not statistically significant. Data from the gawugaa-gii-mara intervention ( n  = 162 written responses) revealed students were challenged by self-reflexivity. There was a disconnect between what students had learnt ( gawugaa ), what they had felt ( gii ) and how this would be applied in professional practice ( mara ). Conclusions: The First Peoples-led, emotions-based pedagogical intervention was brief, meaningful and effective. As students grappled with their emotional connection to self-reflexivity as well as their ability to translate new knowledge into culturally safe practice, these offer important avenues for future research. Highlights: Facilitating health students' development towards cultural safety is emotionally laden and complex. A First Peoples-led emotion-based pedagogical intervention was evaluated. Compared to pre-course responses, there was a large change in students' Witnessing scores. Self-reflexivity was an uncomfortable process reported by students. There was a disconnect between students learning and feeling, and intended practice.